Six Open Debates on Sumak Kawsay - Hidalgo-Capitán, Antonio Luis (2014)
This essay seeks to shed light on six open debates about sumak kawsay: Its meaning, translation, origin, cultural referent, relation with development, and direction. Such debates are analyzed from the premise that the authors who participate in them do so from different cultural paradigms (Andean worldview, modernism, or post-modernism) and from different schools of thought (socialist and statist, indigenist and “pachamamista”, or ecologist and post-developmentalist).